FAKTOR PENENTU DIVIDEN DAN BIAYA KEAGENAN SERTA PENGARUHNYA PADA NILAI PERUSAHAAN - Isti Fadah (Jurnal Keuangan dan Perbankan, 2010)
The goals of the research were to know about ownership structure, cash dividend policy and agency cost, toknow the effect of ownership structure, risk and free cash flow to cash dividend and agency cost and to knowthe effect of cash dividend and agency cost to corporate value in Indonesian Stock Exchange. To find thebest measurement of latent variable used was confirmatory analysis. To test causality relationship, it usedstructural equation model. The result of confirmatory analysis showed that the best measurement of cashdividend policy variable was dividend payout ratio while for agency cost was selling and general administrativeratio. Before millennium era, risk had a significant effect to cash dividend. Risk had a significanteffect to agency cost and a significant effect to firm value. In Millennium era, risk had a significant effectto cash dividend. Risk had a significant effect to agency cost and cash dividend had a significant effect tofirm value. The test result on two different time horizons had a consistency result. It could be seen on test ofgoodness of fit and path analysis gave a consistent result.